SNX10 mutations define a subgroup of human autosomal recessive osteopetrosis with variable clinical severity. (17th April 2013) - Pangrazio, Alessandra; Fasth, Anders; Sbardellati, Andrea; Orchard, Paul J; Kasow, Kimberly A; Raza, Jamal; Albayrak, Canan; Albayrak, Davut; Vanakker, Olivier M; De Moerloose, Barbara; Vellodi, Ashok; Notarangelo, Luigi D; et al.
Abstract Human Autosomal Recessive Osteopetrosis (ARO) is a genetically heterogeneous disorder caused by reduced bone resorption by osteoclasts. In 2000, we found that mutations in the TCIRG1 gene encoding for a subunit of the proton pump (V‐ATPase) are responsible for more than one‐half of ARO cases. Since then, five additional genes have been demonstrated to be involved in the pathogenesis of the disease, leaving approximately 25% of cases that could not be associated with a genotype. Very recently, a mutation in the sorting nexin 10 (SNX10) gene, whose product is suggested to interact with the proton pump, has been found in 3 consanguineous families of Palestinian origin, thus adding a new candidate gene in patients not previously classified. Here we report the identification of 9 novel mutations in this gene in 14 ARO patients from 12 unrelated families of different geographic origin. Interestingly, we define the molecular defect in three cases of "Västerbottenian osteopetrosis, " named for the Swedish Province where a higher incidence of the disease has been reported. In our cohort of more than 310 patients from all over the world, SNX10‐dependent ARO constitutes 4% of the cases, with a frequency comparable to the receptor activator of NF‐κB ligand (RANKL), receptor activator of NF‐κB (RANK) and osteopetrosis‐associated transmembrane protein 1 (OSTM1)‐dependent subsets. Although the clinical presentation is relatively variable in severity, bone seems to be the only affected tissue and the defect can be almost completely rescued by hematopoietic stem cell transplantation (HSCT). These results confirm the involvement of the SNX10 gene in human ARO and identify a new subset with a relatively favorable prognosis as compared to TCIRG1‐dependent cases. Further analyses will help to better understand the role of SNX10 in osteoclast physiology and verify whether this protein might be considered a new target for selective antiresorptive therapies. © 2013 American Society for Bone and Mineral Research.